The Sexually Transmitted Infections Prevention and Care Project, Zimbabwe - World Bank (Washington, DC, 2012)
To quickly and effectively, estimate the medications needed to treat sexually transmitted diseases (STDs) and AIDS-related infections over a five year period, procure the drugs on international tender and survey drug availability among facilities before and after the procured medications arrive in country and are distributed. The Sexually Transmitted Infections (STIs) Prevention and Care Project in Zimbabwe has decreased costs for pharmaceuticals by 60 percent and increased the availability of STI drug in health facilities from 68 percent to 89 percent within the first two years of the project.